Factors that Influenced the Effectiveness of Transfer of Technology (TOT) Programme among Rubber Small Holder in Malaysia - Nalini, Arumugam; Wan Musa, Wan Muda; Izah, Mohd Tahir (2014)
This study aimed to determine the factors that influence the effectiveness of TOT programme among rubber small holders in Terengganu, Malaysia. 200 respondents were involved in the study from seven districts of Terengganu, namely Kuala Terengganu, Maran, Besut, Setiu, Hulu Terengganu, Dungun and Kemaman. Multiple regression was employed. Six factors were employed as independent variables: Understanding about technology, involvement in TOT programmes in group category, involvement in TOT programmes in individual category, effective of TOT programmes in group category, effective of TOT programmes in individual category and frequency of contacts between extension agents with smallholders. The results of the study revealed that all these variables had a positive significant relationship with the effectiveness of technology transfer. These findings could be used by relevant authorities and organizations to plan more comprehensive and strategic programmes in technology transfer activities to rubber smallholders in Malaysia.